Family support and fluid restriction adherence among hemodialysis patients - Sandy Sulistiawati; Moch Aspihan; Iskim Luthfa (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Chronic Kidney Disease (CKD) is a chronic health problem that requires continuous hemodialysis therapy. The success of hemodialysis therapy is strongly influenced by patient compliance with fluid intake restriction to prevent complications such as fluid overload and increased Interdialytic Weight Gain (IDWG). One important factor that plays a role in improving patient compliance is family support. Purpose: To determine the relationship between family support and compliance with fluid intake restriction among hemodialysis patients. Method: A quantitative design with a cross-sectional approach and a descriptive correlational method. The research sample consisted of 100 hemodialysis patients selected using a total sampling technique. Data were collected using the Family Support Scale (FSS) to measure family support and The Fluid Control in Hemodialysis Patients Scale (FCHPS) to measure compliance with fluid intake restriction. Data analysis was conducted using univariate and bivariate analysis with the Somers' d test. Results: Data indicated that most respondents had good family support (91%) and a high level of compliance with fluid intake restrictions (90%). Furthermore, bivariate analysis demonstrated a strong, positive, and significant relationship between family support and adherence to fluid intake restrictions among hemodialysis patients (p = 0.008, r = 0.631). Conclusion: A significant relationship between family support and compliance with fluid intake restriction in hemodialysis patients. Optimal family support plays an important role in improving patient compliance; therefore, nurses and healthcare professionals are expected to actively involve family members in education and management of hemodialysis patient care.